Utilization of Test Instruments Using Safe Exam Browser for Scientific Literacy Seen From The Perspective of Students - Gina; Ramadani; Diniyah Rizkiyanti Zebua (Yayasan Nurul Yakin Bunga Tanjung, 2024)
The research that has been carried out aims to see how students view test instruments that use safe exam browser to measure students' scientific literacy skills on virus material in biology learning. The population of this study was MAN I Kerinci students in class X who had studied virus material in biology lessons. This sampling was used because 20 students felt it was sufficient to create a knowledge picture of their general scientific literacy abilities. The data analysis technique in this research uses a questionnaire with a Likert scale. The analysis will be conducted using the understanding or theory of student response criteria from the questionnaire given. The categorization is divided into 4 categories and also analyzed in the form of percentages and analysis of interviews with several randomly selected students and direct observation. The results of the research show how students view the test instruments given, where the average student gave a score of 86.1%, with an average score of 3.44 in the pretty good category. The pretty good category details that the virus material provided by the teacher from the student's perspective is pretty good on the test instrument used, namely 86.2% with a response criterion of 3.45, including the pretty good category, then the language used also has an average student response value of 86.2% with a response criterion of 3.44 with a response category of pretty good.